A randomized comparison study of conventional normal saline and silver nanocrystalline gel as topical wound dressings in non-healing wounds - Mahadev, V. (International Surgery Journal, 2021)
Background: Non-healing wounds and chronic ulcers are being consequence of the abnormality in healing process and disturbance in the recovery pathway. Picking an ideal choice of topical application and dressing helps in enhancing the wound heal in addition to the antibiotics administration. To identify the outcome of topical dressing in chronic ulcers by using, silver nanocrystalline gel dressing (AgNP) and conventional normal saline dressing (NS). Methods: This study was an open label randomized study in patient with chronic non-healing wound. The wound healing outcomes of two different dressing methods were compared, which was evaluated by independent assessor. The primary outcome is area reduction of wound and duration of healing. The secondary outcome is the formation of healthy granulation, slough and discharge and wound site infection control. Results: The outcome of AgNP and conventional NS dressing was compared. The 100 patients with non-healing wounds were randomized in the ratio of 1:1. The primary outcome was study group had better area of reduction of 41.97% (SD-7.41) with statistical significance (p<0.0001) and mean duration of healing, 15.64 weeks. The secondary outcome of healthy granulation tissue and reduced slough and discharge at the end of 3 weeks with topical silver nanocrystalline dressing was significant. Conclusions: Topical silver nanocrystalline dressing shall be an effective dressing option to achieve apposite recovery of healing process in non-healing wounds.